2022
DOI: 10.1039/d0cs00569j
|View full text |Cite
|
Sign up to set email alerts
|

Metal-containing organic compounds for memory and data storage applications

Abstract: This review gives an overview of the recent advances of metal-containing organic compounds in memory and data storage applications. The challenges and future research directions of the field are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 219 publications
(227 reference statements)
0
57
0
1
Order By: Relevance
“…Notably, these compounds also show good thermal stability, with an onset decomposition temperature over 300 °C (Figure S9). Several studies have revealed that the Joule heat produced in organic ReRAM device operation may lead to the decomposition and/or the instability of active materials. , Therefore, the outstanding heat-resistance behaviors of these heteroaromatic molecules benefit to guarantee the longevity of the materials during long-term operation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, these compounds also show good thermal stability, with an onset decomposition temperature over 300 °C (Figure S9). Several studies have revealed that the Joule heat produced in organic ReRAM device operation may lead to the decomposition and/or the instability of active materials. , Therefore, the outstanding heat-resistance behaviors of these heteroaromatic molecules benefit to guarantee the longevity of the materials during long-term operation.…”
Section: Resultsmentioning
confidence: 99%
“…With the increasing demand on ultrahigh-density data-storage (UHDDS) systems in advanced information processors and flexible electronics, the prospect of adopting organic materials as memory medium in UHDDS semiconductors has aroused more attention. Organic materials afford attractive merits of low cost, easy processing, excellent miniaturization potential, and few environmental footprints as compared to inorganic electronics. In addition, organic memory materials hold promise to realize UHDDS since their structures can be tuned at the molecular level to induce multiple resistive switching characteristics. Attributed to their structural adjustability and scalability, not surprisingly, organic molecules have been demonstrated as promising materials for high-performance semiconductors such as organic photovoltaics, , organic field-effect transistors, , organic light-emitting diodes, , and organic batteries. , Their application in organic resistive random-access memory (ReRAM) is currently also under progress.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the choice of functional materials can be transitioned from semiconductor materials to organic materials, biomaterials and polymer, thereby preparing the ReRAM devices with flexible properties, laying the foundation for wearable electronics. 196–205…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the choice of functional materials can be transitioned from semiconductor materials to organic materials, biomaterials and polymer, thereby preparing the ReRAM devices with flexible properties, laying the foundation for wearable electronics. [196][197][198][199][200][201][202][203][204][205] In addition, the preparation of implantable electronic devices is an indispensable key technology in biomedicine, which is also an important support for the development of biomedicine. In many previous studies, it has been found that biomemristors have huge potential applications as implantable devices.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, organic resistive switching memory (ORSM) based on organic materials possesses unique merits, such as compatibility with large-area solution processing, mechanical flexibility, possibility of multilevel storage, and easy modulation by molecular design and synthesis strategy. It has been reported that single-component organic molecule, , multicomponent organic molecules, , and organic–inorganic hybrid materials , present resistive switching effect through charge transfer, trapping, conformation change, redox reaction, and filamentary conduction. Particularly, the multicomponent organic molecules consisting of small molecule and polymer has been used as the active layer of high-performance ORSM, whose crystallization and phase separation can be restrain .…”
Section: Introductionmentioning
confidence: 99%